A campaign targeting a conserved Hsp70 binding site uncovers how subcellular localization is linked to distinct biological activities. Issue 8 (18th August 2022) - Shao, Hao; Taguwa, Shuhei; Gilbert, Luke; Shkedi, Arielle; Sannino, Sara; Guerriero, Christopher J.; Gale-Day, Zachary J.; Young, Zapporah T.; Brodsky, Jeffrey L.; Weissman, Jonathan; Gestwicki, Jason E.; Frydman, Judith
Summary: The potential of small molecules to localize within subcellular compartments is rarely explored. To probe this question, we measured the localization of Hsp70 inhibitors using fluorescence microscopy. We found that even closely related analogs had dramatically different distributions, with some residing predominantly in the mitochondria and others in the ER. CRISPRi screens supported this idea, showing that different compounds had distinct chemogenetic interactions with Hsp70s of the ER (HSPA5/BiP) and mitochondria (HSPA9/mortalin) and their co-chaperones. Moreover, localization seemed to determine function, even for molecules with conserved binding sites. Compounds with distinct partitioning have distinct anti-proliferative activity in breast cancer cells compared with anti-viral activity in cellular models of Dengue virus replication, likely because different sets of Hsp70s are required in these processes. These findings highlight the contributions of subcellular partitioning and chemogenetic interactions to small molecule activity, features that are rarely explored during medicinal chemistry campaigns. Graphical abstract: Highlights: Distinct Hsp70 sub-networks are targeted by chemically related inhibitors Closely related Hsp70 inhibitors display distinct subcellular localizations Differently localized Hsp70 inhibitors have anti-cancer versus anti-viral activities Subcellular localization may contribute to low toxicity of certain Hsp70 inhibitors Abstract : Specific targeting of distinct Hsp70 sub-networks could be used to treat different diseases, such as cancer and virus infection, while minimizing side effects. Here, Shao and Taguwa et al. address the challenge of designing disease-specific inhibitors by taking advantage of the subcellular distributions of closely related Hsp70 inhibitors.